2019
DOI: 10.3892/ol.2019.10260
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of NCAPH is upregulated and predicts a poor prognosis in prostate cancer

Abstract: Prostate cancer (PCa) is one of the most frequently diagnosed types of cancer worldwide. However, there remains a lack of accurate biomarkers to predict the outcome of PCa. Non-SMC condensin I complex subunit H (NCAPH) encodes a regulatory subunit of the non-structural maintenance of chromosomes condensin I complex. The present study aimed to investigate whether NCAPH may be a novel diagnostic marker for PCa by analyzing public datasets, including GSE17951, GSE55945 and a dataset from The Cancer Genome Atlas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 31 publications
(40 reference statements)
0
43
0
Order By: Relevance
“…NCAPH encodes a regulatory subunit in the non‐SMC condensing I complex and is required for the conversion of interphase chromatin into condensed chromosomes . Previous studies have revealed that abnormal expression of NCAPH is associated with colon cancer and prostate cancer . However, there have been no relevant reports about the clinical relevance and functional role of NCAPH in HCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NCAPH encodes a regulatory subunit in the non‐SMC condensing I complex and is required for the conversion of interphase chromatin into condensed chromosomes . Previous studies have revealed that abnormal expression of NCAPH is associated with colon cancer and prostate cancer . However, there have been no relevant reports about the clinical relevance and functional role of NCAPH in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…9 Previous studies have revealed that abnormal expression of NCAPH is associated with colon cancer and prostate cancer. 10,11 However, there have been no relevant reports about the clinical relevance and functional role of NCAPH in HCC. In this study, we aimed to explore NCAPH expression in HCC tissues and investigate the functions of NCAPH in HCC cells.…”
Section: Introductionmentioning
confidence: 99%
“…In PCa, MCPH23 interacts with a variety of proteins during the regulation of PCa-associated cell cycles. These proteins include Aurora kinase A, Aurora kinase B, and cyclin-dependent kinase 1 [38]. Consistently, the deletion of low-density lipoprotein-related receptor 5 inhibits liver cancer cell proliferation via destabilizing MCPH24 in a β-catenin-independent way [111].…”
Section: Mcph Gene Regulate Neurogenesis and Carcinogenesis Through Rmentioning
confidence: 77%
“…The knockdown or inhibited expression of these genes may be a potential therapeutic method for cancer treatment [31][32][33]. In addition, the overexpression of MCPH2, MCPH5, MCPH7, MCPH14, MCPH20, MCPH21, MCPH23, and MCPH24 is associated with aggressiveness and poor outcome in patients with cancer [28,[34][35][36][37][38][39]. However, MCPH1 and MCPH15 are downregulated in tumor tissues or cancer cell lines and are considered as novel tumor suppressor genes [40,41].…”
Section: Some Mcph Genes Can Be Considered As Potential Cancer Biomarmentioning
confidence: 99%
“…NCAPH is upregulated in endometrial cancer and associated with poor clinicopathologic characteristics [5]. Overexpression of NCAPH is upregulated and predicts a poor prognosis in prostate cancer [6]. However, NCAPH and RFC4 subnetworks containing CDKN3 (feedback) has not been explored for the novel molecular and cellular mechanisms of HCC (HBV or HCV) related cancer development from high UNG-activated upstream network.…”
Section: Introductionmentioning
confidence: 99%